Konservasi Entomofaga dan Polinator di Rawa Lebak untuk Mendukung Keberlajutan Pertanian di Lahan Suboptimal - Herlinda, Siti; Sari, Jelly Milinia Puspita (Seminar Nasional Lahan Suboptimal, 2023)
Herlinda, S.,  & Sari, J.M.P.S. (2023). Conservation of entomophages and pollinators in freshwater swamps to support agricultural sustainability on suboptimal lands. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 1-24).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Suboptimal wetlands in Indonesia consist of freshwater swamp, tidal lowland and peatland. The freshwater swamp can generally be used to grow food crops, vegetables and plantations. In the freshwater swamp of South Sumatra, farmers grow vegetables using the "surjan" (rice-field bund) system in addition to rice and corn. The cultivation of vegetables between rice fields in the "surjan" system is very beneficial to the balance of the ecosystem, especially by increasing the diversity of flora, which can increase the diversity of fauna, especially predatory arthropods and parasitoids (entomophagous insects) and pollinators. The abundance of these entomophages and pollinators needs to be increased through conservation. This paper explains the approach to conservation of entomophagous and pollinators by 1) reducing disturbance factors, 2) increasing the habitats and food resources (niches) needed by entomophagous and pollinators. This literature review has shown that in freshwater swamps, factors that disrupt the lives of entomophagous and pollinating insects include land burning, spraying of synthetic insecticides and herbicides, intensive cultivation (full tillage), and clean cultivation. Factors that disrupt the lives of entomophagous insects and pollinators should be avoided by not burning land, not spraying synthetic insecticides and herbicides, and minimising tillage to allow annual wild plants to flower on embankments. Flowering annual wild plants provide food for entomophagous insects and pollinators. However, many factors that support the life of entomophages and pollinators in freshwater swamps have also been identified and have been implemented by local farmers and have become local wisdom. The intercropping of long beans and chillies and the planting of flowering vegetables such as bitter melon, cucumbers, long beans and squash could support the sustainability of entomophages and pollinators by providing niches (food, nectar and pollen) and alternative host insects and prey for predators. The use of cover crops or straw mulch on chilli fields could provide habitat for predatory arthropods. Finally, entomophages and pollinators can be conserved by reducing and preventing activities that threaten their lives and by increasing space/habitat and food resources.